The influence of gender on the practice of physical activity in high school adolescents in the city of Manaus - de Souza Bezerra, Ewertton; Borba Neves, Eduardo; Rossato, Mateus; Libardoni dos Santos, João Otacilio; Nahas, Markus Vinícius; dos Santos Puga Barbosa, Rita Maria (O Mundo da Saúde, 2016)
Obesity is a public health problem that has been growing, especially in developing countries. It is associated with genetic factors as well as with cultural factors, overeating, and leading a sedentary lifestyle. The aim of this study was to compare sedentary behaviors and levels of physical activity, based on gender, among high school teenagers studying in the state public school system in the city of Manaus, AM, Brazil. The final sample consisted of 864 adolescents of both genders within the ages of 15 and 19 years old. The information was collected by means of a formulated questionnaire and adapted based on COMPAC2. The results were presented using descriptive statistics and a comparison between groups (male and female) was performed using a chi-squared test. The male student group (M) presented higher levels of participation in the physical activities and presented more time dedicated to these activities than the female group (F) which stated preference for computer use and participation in cultural activities. Moreover, 64.3% of the young men and 35.5% of the young women claimed to dedicate between 30 and 60 minutes or more per day to the practice of physical activity. The most used means of transportation to and from school was on foot (M: 62.3%; F: 57.8%). In regards to sedentary behavior, 60% of those assessed stated that they spend more than 2 hours watching television programs each day and 52% of the young men and 42.8% of the young women stated the use of a computer for more than 2 hours each day. The results reveal that the practice of physical activity and sedentary behavior is gender dependent, since the female students practiced less physical activities and therefore presented more sedentary habits.